Studi Etnobotani Tumbuhan Obat Di Desa Perajen Kecamatan Banyuasin I Kabupaten Banyuasin - Trimin Kartika; Syaiful Eddy; Rezki Khairani (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Research on Plant Ethnobotany Study in Perajen Village, Banyuasin 1 District, Banyuasin Regency, was conducted from June to July 2020. The research objective was to analyze the types of plant ethnobotany with medicinal properties and plant parts used as medicine. The study used a descriptive survey method with direct observation in the field. The method used was descriptive exploratory with interviews and field identification. The results showed that the types of medicinal plants from the spermatophyte division consisted of 2 classes, 15 orders, 17 families, 22 genera and 22 species, 49 types of diseases treated by medicinal plants, utilization of plant parts that are often used as traditional medicines by the community. Perajen Village in ethnobotany, namely leaves of 13 species of plants (35.1%), flowers, fruit, seeds, rhizomes, and roots of 3 species each (8.1%), stems, bark, sap, 2 species each. (5.4%), while the least used by the community is gel, water, tubers for each 1 species (2.7%), processing plant parts as medicine is often done by boiling.